SHORTEST ROUTE SEARCH TO ACCOMMODATIONS NEAR MANDALIKA CIRCUIT USING DIJKSTRA'S ALGORITHM AND ANDROID-BASED LOCATION-BASED SERVICE - Moch. Syahrir; Ahmad Subandi Azmi; Kurniadin Abd. Latif; Pahrul Irfan (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
The development of mobile technology, particularly on the Android platform, has created significant opportunities for real-time, location-based applications. One important implementation is the use of Location Based Service (LBS) in the tourism sector to help tourists efficiently find strategic locations. This study focuses on developing an Android-based LBS application that integrates the Dijkstra Algorithm to determine the shortest route to accommodations around the Mandalika Circuit area, Kuta Beach, Lombok, a leading destination for MotoGP events in Indonesia. The system development adopts the waterfall model, consisting of requirement analysis, system design, implementation, and testing. In the analysis phase, user needs related to accommodation information and route navigation are identified. The design phase includes system architecture, user interface, and digital map integration. Implementation is carried out by developing an Android application capable of accessing real-time location data and processing route calculations using the Dijkstra Algorithm to produce the most efficient path. The resulting application displays the distribution of nearby accommodations, provides travel distance information, and offers optimal route guidance that can be directly accessed by users. System testing shows that the application runs according to the defined functional requirements. Additionally, evaluation using a Likert-scale questionnaire indicates a user satisfaction level of 84%, reflecting good acceptance and usability. In conclusion, this research successfully implements LBS technology combined with the Dijkstra Algorithm in a mobile application, providing practical solutions for tourists visiting the Mandalika Circuit area.